1973
DOI: 10.1017/s0022112073001151
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of free and forced convection in horizontal tubes in the transition regime

Abstract: Experimental investigations of the heat transfer by combined free and forced convection to water in a horizontal tube with a uniform heat flux have revealed many interesting features of the transition from laminar to turbulent flow. Fluctuations in fluid temperature and overall pressure drop variations facilitated the study of the transition regime.The first phase of the experiments studied the extreme cases of combined forced- and free-convection transition regimes. For forced convection without heat transfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

1983
1983
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 11 publications
2
8
0
Order By: Relevance
“…They observed that when the product of the Reynolds and Rayleigh number was large, the secondary flow caused the critical Reynolds numbers to approach the same value, whether the turbulence level at the entrance of the tube was high or low. Nagendra (1973) found similar findings while performing extensive transition regime tests.…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…They observed that when the product of the Reynolds and Rayleigh number was large, the secondary flow caused the critical Reynolds numbers to approach the same value, whether the turbulence level at the entrance of the tube was high or low. Nagendra (1973) found similar findings while performing extensive transition regime tests.…”
Section: Introductionsupporting
confidence: 66%
“…Nagendra (1973) found that the greater the disturbance, the earlier transition occurs. Ghajar and Madon (1992) performed an extensive study into the effect of three different types of inlets on the critical Reynolds number during isothermal, fully developed flow.…”
Section: Introductionmentioning
confidence: 99%
“…Nagendra [6] found that the greater the disturbance, the earlier transition occurs. Ghajar and Madon [7] performed an extensive study into the effect of three different types of inlets on the critical Reynolds number during isothermal fully developed flow.…”
Section: Introductionmentioning
confidence: 99%
“…A considerable amount of work has been done to assess the effect of buoyancy on forced convection between horizontal parallel plates (Osborne and Incropera 1985a;Osborne and Incropera 1985b) and in horizontal tubes (Hieber 1982;Nagendra 1973). Nusselt numbers for these mixed convection cases are calculated from the well-known formula for mixed convection in general (Churchill 1977)…”
Section: Mixed Convection and Turbulence In The Liquidmentioning
confidence: 99%
“…3.16, typical Reynolds numbers in the liquid film are well below the transition value to induce hydrodynamic turbulence. However, as the Rayleigh number in the liquid film increases, the flow can transition due to thermal turbulence (Nagendra 1973). When calculating the liquid film thickness in the evaporator, the heat pipe model assumes a laminar liquid flow.…”
Section: Mixed Convection and Turbulence In The Liquidmentioning
confidence: 99%